The design of the green building in construction - Mat Alim, Mohd Izzat; Osman, Nor Hasni; Ahmad, Azhar (2015)
LEED aims to improve the environment performance and yield economic gains in building construction.Green building built to protect the environment.It is built on an area of climatic conditions affecting the constructions site buildings.The Green buildings give a more benefits in construction industry and can be categorized in three groups, such as environmental, economic and social.The design of the green building in construction is a very important for building industry. Design phase of the project in construction includes four steps, such as pre-design, concept design, design development and final design.The designer of the project should be expert or have knowledge in a green building concept.This knowledge is very important factor in gaining this quality and accuracy of the existing physical aspects of a project site.Green building design phase is essential for getting features that aid in keeping the surrounding environment. Design phase is an important phase as it affects the structure of the building to meet green building standards or otherwise.